Translanguaging and trans-semiotising in a CLIL biology class in Hong Kong: whole-body sense-making in the flow of knowledge co-making. Issue 3 (2nd October 2019) - Wu, Yanming (Amy); Lin, Angel M. Y.
ABSTRACT: While translanguaging research has been gaining currency worldwide, calls have been made for deepening its theorisation and providing more systematic pedagogical guidance. To contribute to this discussion, this study is informed by a fluid, distributed, dynamic process view of human meaning-making. Through a fine-grained multimodal analysis of classroom activities and interactions, it elucidates the translanguaging/trans-semiotising practices of an experienced science teacher trying out a CLIL (Content and Language Integrated Learning) approach inspired by the Multimodalities-Entextualisation Cycle (MEC) in a Grade 10 biology class in Hong Kong. Post-lesson interviews and survey indicated that such practices generated a positive impact on the students in the continuous flow of knowledge co-making. Implications of the study for furthering the theorisation and practices of translanguaging/trans-semiotising will be discussed.